(untitled) (Journal of Engineering, 2024)
This study’s primary objective is to examine the structural behavior of using 2C-Cold produced. Section Castellated beams when subjected to monotonic load till failure. The experimental program testing. Seven Fabricated samples of castellated steel beams and one sample, which is a non-castellated steel beam (reference beam), were tested as supported beams under concentrated loads at two points over a clear span length (1730 mm). All castellated steel beams were similar in all properties and dimensions except the breadth of the upper and lower flanges. The current study considers the implications of modifying the width of the top and bottom flanges on how these beams behave. The findings showed that the ratio of the tested Castellated beams’ ultimate load-carrying capacity to the non-castellated reference beam (R1) ranged from 99.3 to 117.2%, and the ratio of the tested beams’ ultimate deflection to the same reference beam (R1) ranged from 72.6 to 103.2%. Increasing the breadth of the top and bottom flanges has a direct relationship with castellated beam stiffness and ultimate load. Finally, adjusting the flange width between the top and bottom flanges reduces castellated beam rigidity and ultimate load.